Hubungan Antara Stres Akademik dengan Prokrastinasi Akademik Pada Mahasiswa Program Studi Keperawatan - Novi Widyastuti Rahayu; Dewi Novita Sari (Fakultas Ilmu Keperawatan Universitas Klabat, 2023)
This study aimed to determine the relationship between academic stress and academic procrastination in STIKES Notokusumo Yogyakarta students. The subjects of this study were 134 students of the Level 2 nursing education program from 4 different classes. This study used a quantitative data collection method using measuring devices in the shape of an academic procrastination scale and an academic stress scale. The Pearson Product Moment Correlation method of data analysis was employed in this investigation. According to the study, academic stress and procrastination have a significant inverse association. This is demonstrated by the correlation coefficient (r), which is -0.182 and has a significant level of 0.035 (p 0.05). This indicates that learning procrastination increases with reduced learning stress levels, while decreasing learning stress levels increases learning procrastination. The effective ratio of academic procrastination and academic stress is 3.3%, which means 3.3% of academic stress can reduce the occurrence of academic procrastination, while other behaviors are impacted by things like self-control or poor time management, resulting in delays. The findings of this study can be applied to student education to improve motivation among students. Other factors that should have been looked at in this study can be added by future researchers. Abstrak Memahami hubungan antara stres akademik dan penundaan akademik siswa STIKES Notokusumo Yogyakarta menjadi tujuan dari studi ini. Subyek penelitian ini adalah 134 mahasiswa program pendidikan keperawatan Tingkat 2 dari 4 kelas yang berbeda. Penelitian ini menggunakan metode pengumpulan data kuantitatif dengan instrumen berupa skala prokrastinasi akademik dan skala stres akademik. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik Korelasi Pearson Product Moment. Berdasarkan hasil analisis, ditemukan adanya hubungan negatif yang signifikan antara stres akademik dengan prokrastinasi akademik. Hal ini ditunjukkan dengan koefisien korelasi (r) = -0,182 dengan nilai signifikansi 0,035 (p < 0,05). Artinya semakin rendah stres belajar maka semakin tinggi prokrastinasi belajar, sebaliknya semakin tinggi stres belajar maka semakin rendah prokrastinasi belajar. Rasio efektif prokrastinasi akademik dan stres akademik adalah 3,3% yang berarti 3,3% stres akademik dapat mengurangi terjadinya prokrastinasi akademik, sedangkan sisanya dipengaruhi oleh faktor lain seperti pengendalian diri atau manajemen waktu yang kurang baik, sehingga terjadi keterlambatan. Rekomendasi penelitian ini dapat digunakan sebagai dasar pelatihan siswa untuk meningkatkan motivasi belajar siswa. Peneliti selanjutnya dapat menambahkan variabel lain yang tidak diteliti dalam penelitian ini.